Alcohol Abuse Enhances Pulmonary Edema in Acute Respiratory Distress Syndrome - Berkowitz, David M. (Alcohol Clin Exp Res, 2009)
BACKGROUND: Pulmonary edema is a cardinal feature of the life-threatening condition known as Acute Respiratory Distress Syndrome (ARDS). Patients with chronic alcohol abuse are known to be at increased risk of developing and dying from ARDS. Based upon preclinical data, we hypothesized that a history of chronic alcohol abuse in ARDS patients is associated with greater quantities and slower resolution of pulmonary edema compared to ARDS patients without a history of alcohol abuse. METHODS: A PiCCO™ transpulmonary thermodilution catheter was inserted into 35 patients within 72 hours of meeting American European Consensus Criteria definition of ARDS. Pulmonary edema was quantified as extravascular lung water (EVLW) and measured for up to 7 days in 13 patients with a history of chronic alcohol abuse and 22 patients without a history of chronic alcohol abuse. RESULTS: Mean EVLW was higher in patients with a history of chronic alcohol abuse (16.6mL/kg vs. 10.5mL/kg, p<0.0001). Patients with alcohol abuse had significantly greater EVLW over the duration of the study (RM-ANOVA p=0.003). There was a trend towards slower resolution of EVLW in patients with a history of alcohol abuse (a decrease of 0.5mL/kg vs. 2.4mL/kg, p=0.17) over the study period. A history of alcohol abuse conferred a greater than three-fold increased risk of elevated EVLW [OR 3.16, (1.26-7.93)] using multivariate logistic regression analysis. CONCLUSIONS: In patients who develop ARDS, alcohol abuse is associated with greater levels EVLW and a trend towards slower resolution of EVLW. Combined with mechanistic and preclinical evidence linking chronic alcohol consumption and ARDS, targeted therapies should be developed for these patients.